Trajectories of adolescent psychotic-like experiences and early cannabis exposure : Results from a Finnish Birth Cohort Study - Denissoff, Alexander; Mustonen, Antti; Miettunen, Jouko; Alakokkare, Anni Emilia; Veijola, Juha; Scott, James G.; Sami, Musa B.; Niemelä, Solja (Schizophrenia Research, 2022)
Background: Longitudinal studies examining the effect of cannabis exposure (CE) on the prognosis of adolescents with psychotic-like experiences (PLEs) are scarce. We examined trajectories of mental health in adolescents with PLEs and cannabis exposure. Methods: The Northern Finland Birth Cohort 1986 (n = 6552) with linkage to nationwide register data was used. Information on lifetime cannabis exposure was collected when participants were aged 15/16. Register-based outcome data on diagnoses made in clinical practice were obtained until age 33. Logistic regression was used to study the association of PLE/CE patterns and subsequent psychiatric disorders. The group with neither PLEs nor CE was utilized as the reference group. Parental psychiatric disorders, family structure, sex, frequent alcohol intoxications, daily smoking and illicit substance use other than cannabis were adjusted for. Results: In all, 6552 subjects (49.2 % males) were included in analysis. PLEs with cannabis exposure were associated with any psychiatric disorder (OR = 2.59; 95 % CI 1.82–3.68), psychotic disorders (OR = 3.86; 95 % CI 1.83–8.11), mood disorders (OR 4.07; 95 % CI 2.74–6.04), depressive disorders (OR = 4.35; 95 % CI 2.93–6.48), anxiety disorders (OR = 2.06; 95 % CI 1.34–3.17) and substance use disorders (OR = 2.26; 95 % CI 1.13–4.50) compared to reference group. Effect sizes were greater for group with both PLEs and cannabis use than for group with PLEs only. Conclusions: Early-onset cannabis use is an adverse prognostic marker for adolescents with PLEs after extensive confounder control including other substance use. Peer reviewed